Clinical case of postoperative anesthesia of a patient by using subanesthetic dose of ketamine in severe abdominal pathology - Zaletskyi, B V; Korobko, V A; Dmytriiev, D V (Pain medicine, 2019)
Pain is an inevitable consequence of surgical interventions in children, resulting in great stress and discomfort not only for patients but also for their parents. The intensity of the pain depends not only on the level of injury after the operation, but also on the localization and the nature of the procedure. Management of pain in children is best done through a multimodal approach: opioids, auxiliary drugs such as nonsteroidal anti-inflammatory drugs (NSAIDs) and acetaminophen, anti-neuroleptics such as gabapentin, and regional anesthetic methods. Postoperative anesthesia in abdominal surgery at present is a topical problem in anesthetic practice. In this clinical case, we would like to demonstrate the experience of applying post-operative anesthesia using subnormal dosages of ketamine. The patient was given anesthesia with prolonged infusion of a ketamine solution in a submorbid dose of 0.2 mg/kg/h IV. An assessment of the quality of anesthesia by assessing the level of stress markers, such as blood glucose, cortisol levels, and the assessment of the pain level on the NIPS scale was performed. Conclusion: The use of a ketamine solution in a dose of 0.2 mg/kg/h has a positive effect on treating postoperative pain in patients after severe abdominal surgical interventions. Applying a ketamine solution in a dose of 0.2 mg/kg/h reduces tolerance of the patient to opioid analgesics and the development of hyperalgesia and allodynia.